Comparison of respiratory mechanics and muscle performance between individuals cured from SARS-CoV-2 with home and hospital treatment (Research, Society and Development, 2022)
Introduction: After the discovery made by the Chinese health authorities, identifying the SARS-CoV-2 virus, there was a need for further studies, as it became a pandemic. Even those infected with COVID-19 had mild or asymptomatic symptoms, mainly clinical presentations were respiratory tract disorders and muscle changes during the period in which the individual was infected, undergoing treatment or post-COVID. Thus, the objective of this study was to evaluate and compare the behavior of respiratory mechanics and muscle performance between post-COVID-19 individuals who were hospitalized and those who received home treatment. Method: Evaluation of 13 individuals, aged 25 to 65 years, divided into 2 groups: Group 1 - post diagnosis of COVID-19 undergoing hospitalization and Group 2 - post diagnosis of COVID-19 undergoing home treatment. Both groups outside the isolation period, without risk of contamination. Subjects were evaluated by Manovacuometry, Peak Expiratory Flow and muscle performance. Data presented in the form of mean and standard deviation, compared between groups using the T-Student test with a significance level of 5%. Results: there was a significant difference in the comparison between the averages of MIP of Group 1 between the predicted values (p=0.04), while the other comparisons obtained p>0.05. Conclusion: even with several publications reporting differences in respiratory mechanics and muscle endurance, these differences were not statistically significant in our work, being better presented with a larger sample number and shorter time between COVID-19 infection and assessments.